Aktualisasi Tindakan Kebiri Kimia bagi Pelaku Kriminal Pedofilia: Antara Fiqh Jinayat dan HAM - Muhammad Fashihuddin; Aunur Rofiq; Suwandi (CV. Ulil Albab Corp, 2022)
Violence is a criminal act that threatens humanity and injures vital human rights. Moreover, the child is the main target. This kind of violence needs to be followed up as well as possible so that the same violence does not occur. Therefore, this paper is intended to contribute to the construction of thought from the point of view of fiqh jinayat and human rights. This study uses a normative qualitative method with a fiqh jinayat approach and human rights as a research perspective. The results of this study include: a) chemical castration in fiqh jinayat is classified as a sanction that is not based on syarak rules. This is because castration itself is not strictly legalized by the Shari'a. Therefore, chemical castration cannot be applied, so that it can be applied to the realm of adultery which results in whipping or stoning, homosexuality which results in death, or the trial which consequents punishment; b) chemical castration is very contrary to human rights, both based on the constitutional version of humanity and Islam. This injures human rights, because chemical castration does not actually have a positive effect on the perpetrator, but has a negative effect with quite fatal consequences. Therefore, IDI is reluctant to be the executor of this action, because it violates the medical code of ethics.